2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6943194
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness modeling of industrial robots for deformation compensation in machining

Abstract: In robotic machining applications, the precision of the robot is of great importance. In heavy machining process, the lower stiffness of industrial robots results in greater position errors than that of the CNC machine executing the same process. In this contribution, a new stiffness model with 36 degrees of freedom and nonlinear descriptions are presented together with a new identi cation method. Experimental results outline the potential of the model in machining application. Acknowledgment: The authors woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Given the dynamic properties to compensate the machining errors, Schneider et al [76] developed an elastic solid-state joint-based method which allows to adjust system stiffness in two orthogonal directions independently. Then, a set of experiments were carried by Olof et al [77], of which results showed that a milling accuracy ± 12 μm was achieved in both face and radial milling. Schneider et al…”
Section: Fixed Spindle In Robotic Machining (C1)mentioning
confidence: 99%
“…Given the dynamic properties to compensate the machining errors, Schneider et al [76] developed an elastic solid-state joint-based method which allows to adjust system stiffness in two orthogonal directions independently. Then, a set of experiments were carried by Olof et al [77], of which results showed that a milling accuracy ± 12 μm was achieved in both face and radial milling. Schneider et al…”
Section: Fixed Spindle In Robotic Machining (C1)mentioning
confidence: 99%
“…Linear descriptions of the stiffness inverse cannot describe the nonlinear character of gear deformation, therefore nonlinear functions are used to model the single stiffness. This allows to integrate effects such as backlash and play of the bearings in the model [17]. Complexity of this proposed model is not the definition of DoF, but is the identification of model parameters.…”
Section: Stiffness Modeling and Identification Of Industrial Robotsmentioning
confidence: 99%
“…Industrial robots are being more widely used in a variety of industrial applications, such as handling, palletizing, and some machining applications, including milling, drilling, and friction stir welding (FSW) due to their advantages of large workspace, compact structure, good flexibility, and low cost compared with machine tools. [1][2][3][4] The compliance of reducers and the elasticity of links make the stiffness of the industrial robots worse; the stiffness of a large six-degree-of-freedom (DOF) industrial robot is usually lower than 1 N/ mm; however, the stiffness of a standard computer numerical control (CNC) machine tool is usually higher than 50 N/mm. 5 Due to the relatively low stiffness, industrial robots always suffered from static and dynamical deformations or chatter vibrations induced by external forces applied on the end-effector during the machining process.…”
Section: Introductionmentioning
confidence: 99%